2020
DOI: 10.2139/ssrn.3559773
|View full text |Cite
|
Sign up to set email alerts
|

Are Litigation Outcome Disparities Inevitable? Courts, Technology, and the Future of Impartiality

Abstract: insightful comments. Conflict disclosure: Prescott is a cofounder and has an equity interest in Court Innovations Inc., a company that develops and implements online dispute-resolution systems, including Matterhorn, which the Article discusses and evaluates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Our results suggest that the recollection of positive in-person services taints the perception of virtual services; however, our analysis is based on retrospective cross-sectional data requiring clients to answer questions based on recollections, which may not accurately reflect how they felt about in-person services at the time they were delivered. Research has found procedural justice, and in particular impartiality, to be improved with the use of virtual courts by reducing face-to-face interactions, thereby reducing implicit judicial bias from potentially influencing the decision-making process ( Mentovich et al, 2019 ), which might explain some of the results from our study. For clients using virtual treatment courts, reduced judicial bias could have influenced their experiences, and we suggest future research consider this unmeasured but important outcome for virtual treatment courts.…”
Section: Discussionmentioning
confidence: 77%
“…Our results suggest that the recollection of positive in-person services taints the perception of virtual services; however, our analysis is based on retrospective cross-sectional data requiring clients to answer questions based on recollections, which may not accurately reflect how they felt about in-person services at the time they were delivered. Research has found procedural justice, and in particular impartiality, to be improved with the use of virtual courts by reducing face-to-face interactions, thereby reducing implicit judicial bias from potentially influencing the decision-making process ( Mentovich et al, 2019 ), which might explain some of the results from our study. For clients using virtual treatment courts, reduced judicial bias could have influenced their experiences, and we suggest future research consider this unmeasured but important outcome for virtual treatment courts.…”
Section: Discussionmentioning
confidence: 77%
“…This latter option eliminates the need to take time off work, travel to a courthouse, and arrange for childcare. It also helps parties feel more comfortable and confident by allowing them to communicate from a familiar environment, in writing, as opposed to relying on real‐time verbal interaction at a courthouse before a judge (Bulinski & Prescott, 2016; Mentovich, Prescott, & Rabinovich‐Einy, 2020; Schmitz, 2019). Furthermore, the communication guardrails, easy‐to‐use online tools, and tailored information that are typically available in asynchronous online court processes can help parties frame their arguments and make their case effectively without relying on legal representation or knowledge of how the law or the legal system work (Bulinski & Prescott, 2021; Prescott, 2023; Sela, 2016; Susskind, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the very features that create opportunities for better access, in particular the remote and asynchronous nature of online communication, may detract from how parties perceive the quality of their interpersonal treatment by the court (and the system) during online proceedings (Mentovich, Prescott, & Rabinovich‐Einy, 2020). The opportunity for rich, real‐time communication among parties and the judge, which includes ongoing dialogue, body language, and tone of voice, is supplanted by thin, one‐directional written communication (Sternlight, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The application of technology can exponentially increase access and efficiency 11 and reduce some inequalities. 12 But it also raises new risks and can exacerbate inequalities within dispute resolution processes; 13 for example, regarding data security, 14 unequal access to technology and the Internet, 15 replication of human bias by AI, 16 technologically enhanced repeat player bias, 17 unequal risks with software and platform usage, 18 and a lack of transparency and accountability in the use of technology. 19 Clearly, technology has altered the parameters of our processes and has stimulated valuable research and discussions about its ramifications in ADR and courts.…”
Section: Introductionmentioning
confidence: 99%
“…16 Draper, 2021;Wing, 2017. 17Katsh and Rabinovich-Einy, 2017;Mentovich, Prescott, and Rabinovich-Einy, 2021;. 18 See Barsky, 2016 Wing, 2016.…”
mentioning
confidence: 99%